Chemical constituents, antibacterial, acaricidal and anti-inflammatory activities of the essential oils from four Rhododendron species - He, Jian; Shang, Xiaofei; Dai, Lixia; Yang, Xiaorong; Li, Bing; Wei, Yanming; Zhang, Jiyu; Pan, Hu (Frontiers in Veterinary Science, 2022)
As the ornamental plants and traditional medicines, Rhododendron przewalskii, R. anthopogonoides, R. thymifolium, and R. capitatum are widely distributed in western China. In this paper, the essential oils from these four species were extracted by supercritical extraction and the components were analyzed using headspace solid phase microextraction combined with gas chromatography-mass spectrometry (HS-SPME-GC-MS), the antibacterial, acaricidal and anti-inflammatory activities were investigated. Results showed that R. thymifolium (RTEO) contained the highest yield of 0.99% with 246 compounds, followed by R. capitatum (RCEO, 0.81%) with 290 chemicals, R. anthopogonoides (RAEO, 0.57%) with 302 compounds and R. przewalskii (RPEO, 0.30%) with 294 components. They also exhibited the safety at given doses and have the anti-inflammatory in vitro and in vivo tests via inhibiting the cytokines productions, the acaricidal and antibacterial activities also were found. 4-Hydroxy-3-methylacetophenone from RPEO, α-pinene and β-pinene from RAEO, β-farnesene and germacrone from RTEO, and benzylacetone from RCEO, as main and active components, inhibited the NO content in RAW 264.7 cells induced by LPS. These results indicated that four essential oils have certain medicinal value and laid the foundation for the development of these species as raw materials for the pharmaceutical and perfume industries.